Development of autism spectrum disorder educational module(ASD.EM) for pre-school teachers’ knowledge, belief, identification skills, and self-efficacy to identify children with ASD - Taleb, Sahar Mohammed Taresh (2021)
Being a developing country, there are a few services centers in Yemen for children with ASD; access to services is further impeded by ignorance about this kind of disorder, negative beliefs, and stigmatizing attitudes towards affected children and their families. To increase access to services, care provision is decentralized through task-shifted care by pre-schools workers, such as pre-school teachers (PSTs). The purpose of this study is to evaluate the effect of ASD.EM on pre-school teacher’s knowledge, belief, identification skill and self-efficacy to identify children with ASD in Taiz Yemen. mixed method included questionnaires and open-ended questions was utilized to investigate the impact of ASD.EM on PSTs’ Knowledge (K), Belief (B), Self-Efficacy (SE), and Identification Skills (IS) to identify children with ASD. Cluster randomized trial was used to select 120 PSTs to answer the K, B, SE questionnaires. Participants were randomized for experimental groups (EG=60) and control group (CG=60). Then, forty participants (EG=20, CG=20) were randomly selected from the total sample (120 PSTs) to answer IS open-ended questions. The educational module ASD.EM consists of four structure units divided into 10 sessions with the range of 20 hours. It was implemented to the experimental group while the control group received another educational program related to career development (playing learning strategy) for 20 hours. Data were first collected from the Pre-test and then from the post-test after immediately finishing the ASD.EM sessions. Then, after one month of giving the posttest, data were gathered for a follow-up test. General linear model (GLM) repeated measure was used to compare between group EG &CG in K,B,SE. While, Multivariate analysis of covariance (MANCOVA) was used to assess the effect of ASD.EM on PSTs’ K,B,SE after controlled the covariate variable . Also, the researcher used theme analysis (TA) to explore the PSTs responses for open-ended questions. Data were analysed using SPSS version 25.0 with level of significance at 0.05. The result showed that the EG showed more significant improvement in PSTs K, B, SE than CG. That is, K mean did not differ between EG and CG at pre-test; (mean=82.08 (6.179) vs 81.45 (4.986), F (.618) P=.538). However, in the post-test and follow up test, the EG had a greater increase in PSTs’ K between the groups; for post-test (mean=102.82 (6.329) vs 80.85 (4.547), F (21.836) P=0.001) and for follow up test (mean=103.08 (5.334) vs 81.55 (3.899), F (25.246) P=0.001). B mean did not differ between EG and CG at pre-test (mean=56.67 (7.476) vs 57.20 (7.702), F (-.385) P=.701). However, in the post-test and follow up test, the EG had a greater increase in PSTs’ B between the groups; for post-test (mean=65.13 (3.534) vs 56.40 (7.265), F (8.373) P=000) and for follow up test (mean=65.25 (3.690) vs 56.58 (6.953), F (8.528) P=000). SE mean did not differ between EG and CG at pretest (mean=40.08 (4.256) vs 39.90 (3.948), F (.245) P=.807). However, in the post-test and follow up test, the EG had a greater increase in PSTs’ SE between the groups; for post-test (mean=51.00 (3.086)) vs 40.22 (4.499), F (15.310) P=000), and for follow up test (mean=50.05 (2.752) vs 40.38 (4.614)), F (13.937) P=000). In contrast, MANCOVA results showed no statistically significant difference on PSTs’ K, B, SE based on demographic variables (educational level, teaching experiences) after controlling the covariate variable. Besides, three themes have emerged from the thematic analysis: (I)Ability to identify and name children with ASD, (ii) Ability to describe a child's behavioural problem, and (iii)Decision- recommending for referral to the specialist. Therefore, the findings, confirmed that the ASD.EM effectively improved PSTs’ knowledge, belief, self-efficacy, identification skills to identify children with ASD in Taiz, Yemen.